Microsoft office specialist and microsoft technology associate certification: An integrated curriculum for technical skills validation - PAULINO H. GATPANDAN; MARYLI F. ROSAS; DANIEL DASIG JR (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to provide information on how well college students fared on the Microsoft Office Specialist (MOS) and Microsoft Technology Associate (MTA) exams. The MOS and MTA programs offer extensive resources to aid teachers in achieving world-class ICT integration in the classroom.Methodology: Student exam takers’ Certiport results from De La Salle University-Dasmarinas in Dasmarinas, Cavite, Philippines, were analyzed using a quantitative-descriptive secondary data analysis.Findings: There was a 34% success rate for those attempting certification, a 63% failure rate, and a 3% incomplete rate. The results of this test will attest to the student’s readiness for entry-level employment. Teachers and students alike can benefit from this certification program, which makes it simple to test their knowledge of productivity tools via the web.Implications/Novelty: Taking into account the range of the fundamentals and precepts of MOS and MTA, the findings of this research are useful for educational institutions because they can be used as the basis for crafting a program or an improvement plan for the curriculum, facilities, or training geared towards these certifications schemes.